2017
DOI: 10.5539/elt.v10n9p208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Teacher Beliefs and Efficacy for Teaching Writing to Weak Learners

Abstract: The present study investigated the beliefs and efficacy of a teacher teaching English to students who were weak at the language. The objective of the study was mainly to investigate the beliefs and efficacy of the ESL teacher for teaching writing to weak learners. The research was a case study of the English Language teacher teaching Form Three class of students whose English proficiency was very low. An interview was conducted with the teacher to further probe the instructional strategies applied to enhance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…The classroom teachers' text-writing instruction self-efficacy beliefs were generally found to be high. In the literature, while some studies (Berrier, 2009;Mohtar et al, 2017) reported similar results on this variable, others (Graham et al, 2001) indicated that teachers' self-efficacy beliefs in writing instruction are at a moderate level. As a result, though the classroom teachers' knowledge of text-writing instruction is moderate, they appear to believe that they teach it well.…”
Section: Discussionmentioning
confidence: 90%
“…The classroom teachers' text-writing instruction self-efficacy beliefs were generally found to be high. In the literature, while some studies (Berrier, 2009;Mohtar et al, 2017) reported similar results on this variable, others (Graham et al, 2001) indicated that teachers' self-efficacy beliefs in writing instruction are at a moderate level. As a result, though the classroom teachers' knowledge of text-writing instruction is moderate, they appear to believe that they teach it well.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, studies within the realm of language education, such as those by Hasanah (2021) and Nur et al (2021), have delved into the impact of motivational strategies on English language learning, emphasizing the pivotal role of intrinsic motivation in enhancing language proficiency. Additionally, Mohar et al, (2017) explored the effectiveness of various pedagogical approaches in improving writing skills among English language learners, offering insights into effective instructional strategies and interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tulisan yang dihasilkan kemudian diungkapkan melalui keterampilan berbicara. Keterampilan berbahasa tersebut saling berintegrasi dan berpadu menjadi kesatuan yang utuh (Mochtar, 2017).…”
Section: Pendahuluanunclassified
“…Selama proses pembelajaran berlangsung, guru merupakan poin penting dan utama dalam proses pembelajaran. Mochtar (2017) menyatakan bahwa keberhasilan guru memungkinkannya untuk memutuskan untuk melakukan tugas mengajar menulis kepada siswa karena yakin akan kemampuannya. Guru memberikan petunjuk kepada siswa untuk memfasilitasi selama proses pembelajaran.…”
Section: Pendahuluanunclassified